Application Of Confederation Methods, Route reflector And Next hop self On BGP Routing - Gilfan Niando; Iwan Wahyuddin; Andrianingsih Andrianingsih (SISFOTENIKA, 2022)
Advances in communication technology affect the need for larger networks. The bigger the network, the more routes there are. In BGP, the larger the session formed on the AS, the slower the network communication. Some ways to reduce the amount of information in the routing table are to use the confederation method, route reflector and route next hop self. In this study, we will discuss the simulation of the application of the confederation method, route reflector and route next hop self in BGP routing on different AS relationships to reduce the amount of information in the routing table. This study was made to provide a solution for full-mesh conditions in BGP. The application uses GNS3 software to create prototypes and network simulations. So that it can be applied to real networks later. The test is to calculate the forwarding delay, delay and throughput. Based on the experiments conducted, the three methods resulted in 7% lower forwarding delay, 29% lower end-to-end delay, and 26% higher throughput than full-mesh BGP. This proves that these three methods can reduce the routing table and make packet data delivery faster. For further research, it is hoped that it can be applied to real case studies so that effectiveness and efficiency can be assessed as well as the impact of the configuration used in real.